Adoption Behaviour of Chilli Cultivators in Thenmaradchchi - Umashankar, K.; Kalaivani, K. (Faculty of Agriculture University of Jaffna, Sri Lanka, 2010)
Even though chilli as one of the predominant cash crops said to be bringing more income to the farmers, the majority of the farm households have not fully adopted chilli cultivation. The overall objective of this study is to find the degree of adoption of chilli cultivation and the determinant factors of the adoption of chilli cultivation by farmers of Thenmaradchy located in Jaffna district. The samples were selected by using stratified random sampling method. The sampled population represented around 16% of the total chilli cultivators in Thenmaradchchi area. Pretested structured questionnaire was administrated to collect the data from the chilli cultivators. The pair wise correlation between adoption of chilli and other individual variables such as education level, knowledge, age, farming experience, farm size, distance to the market place, capital availability and dummy variable of A.I range. The association between the adoption of chilli cultivation and the determinants were analyzed within the framework of Tobit qualitative regression model. The results revealed that in pair wise correlation significant relationships were found between education level and knowledge, education level and adoption, knowledge and adoption, age and knowledge and experience and adoption. In Tobit qualitative regression model adoption showed significant relationships with education level, farm size, market distance from farm land and capital availability.
Keywords: Chilli; Adoption; Scoring; Tobit